Express each of the following using the summation notation:

a. [2X_{1} +2X_{2} +2X_{3}][5X_{1} +5X_{2} +5X3_{3}]

b. [A_{1 }+ A_{2} + A_{3} +A_{4}]^{2}[B_{1}^{2} + B_{2}^{2} + B_{3}^{2} + B_{4}^{2}]

### Want to see the full answer?

Check out a sample Q&A here*star_border*

## Related Statistics Q&A

Find answers to questions asked by students like you.

Q: For each of the summations given below, use the formula for the sum of the first n integers either…

A: Click to see the answer

Q: For each of the summations given below, use the formula for the sum of the first n integers either…

A: Click to see the answer

Q: 2. Write the summation notation of the following; 5y2 а. 3x,3 Зуз 7y4 4y5 2х23 5x33 ' 3x43 X2 b. 9y1…

A: In the given question we have to write the summation notation of the functions.

Q: For each of the summations given below, use the formula for the sum of the first n integers either…

A: Use the formula of addition of integers to solve this problem.

Q: Write the following expression as a single summation in terms of k. m k Σ m + 1 Σ %3D k + 5 k = 1 m…

A: Click to see the answer

Q: If Given X1=12 X2=19 X3=10 X4=7, then the summation of X equals?

A: The given values are X1=12,X2=19,X3=10,X4=7. The summation of X equals, ∑X=X1+X2+X3+X4=12+19+10+7=48

A: Click to see the answer

Q: Write the following expression as a single summation in terms of k. m + 1 V k m + 1 k + 8 m + 9 k =…

A: To write the given expression as a single summation in terms of K.

Q: each of the summations given below, use the formula for the sum of the first n integers either to…

A: To calculate the sum of the numbers summtion we are going to form a closed summation.Now to do that…

*question_answer*

Q: Find the summation of E3º 12(2r + 5) r3D12

A: Click to see the answer

*question_answer*

Q: 2. Write the summation notation of the following; 4y5 + 3x43 Зуз 7y4 5y2 а. 3x1 2x23' 5x33 27х4 ,…

A: Step:-1 Part (a):- Given that 5 y23 x13 + 3 y32 x23 +7 y45 x33 +4 y53 x43 5 y23 x13 + 3 y32 x23 +7…

*question_answer*

Q: How and why does the first summation in this picture turn into the finall summation?

A: Click to see the answer

*question_answer*

Q: Write each expression in summation notation 2 + 2 +2 + ... + 2 (n 2's)

A: Click to see the answer

*question_answer*

Q: B. Write the summation notation for each expression. (1) 1+3+5+7+. . . +101 (2) a2 + a4 + a6 + ag+ .…

A: Click to see the answer

*question_answer*

Q: Find only 4 terms for the summation: e2xn 2o n2+1 1)

A: Corresponding to each 'n' we have a term.

*question_answer*

Q: 1. Write the following summation as a single summation: 3 (2k – 3) +(4- 5k) k=1 k=1

A: Click to see the answer

*question_answer*

Q: 2. Write the summation notation of the following; 3y3 7y4 4y5 5y2 а. 3x13 + + 2x23 ' 5x33 ' 3x43 X3…

A: Consider the given equations:

*question_answer*

Q: Express the following sum in closed form. (2+3k)² = k 1 Hint: Start by multiplying out (2 + 3k)?.…

A: To write sum in closed form

*question_answer*

Q: Determine the following summation in terms of n: n2 E(2i + 5) i=1

A: Since there are multiple questions posted, we will answer the first question (1). If you want the…

*question_answer*

Q: Write each summation as a series. (1 –2)(1+2) D-0-0-0-01-D-0

A: Click to see the answer

*question_answer*

Q: Write the summation in expanded form. jG + 1) j = 1

A: Expand the summation one by one.

*question_answer*

Q: Find the numerical value of the following expression by finding the pattern. Without using the…

A: This is problem is solved by finding the pattern of the expression

*question_answer*

Q: 2: Evaluate the following summation. Lince x 7X7331

A: Click to see the answer

*question_answer*

Q: Write the following expression as a single summation. S (7k? + 4) + 2· (6k² – 1) = S %3D k = 1 k = 1…

A: Click to see the answer

*question_answer*

Q: Simplify by comnbining the two sums and find an explicit formula. That is, your answer should not…

A: Click to see the answer

*question_answer*

Q: Wht is the sum of this 8.1 - 3.1 x 2.1 + 0.4

A: Click to see the answer

*question_answer*

Q: Evaluate the following sum using generating function 12 + 22 + 32 +........ +r2 +r?

A: As per our company guidelines we are supposed to answer 1st question. Kindly repost the other in…

*question_answer*

Q: Use summation notation and find the total number of offspring for each of the following organisms.…

A: Click to see the answer

*question_answer*

Q: Which of the following summations are written in closed form? [At least one of the choices is in…

A: Which of the following summations are written in closed form

*question_answer*

Q: Transform the following summation by making the change of variable i = k +1: k+n k=0

A: To transform using the change of variable i = k + 1

*question_answer*

Q: Express the sum using summation notation: 1 + 1/2 + 1/4 + 1/8 + ..... + 1/(2n-1)

A: Click to see the answer

*question_answer*

Q: Find the value of the summation. E (2 – 3) = k= 0 of

A: We can find the summation value as below.

*question_answer*

Q: Rewrite 1+2+4+...+229 using summation notation.

A: We need to write the following expression in summation notation 1+2+4+······+229

*question_answer*

Q: Expand each summation. Σ Σ Σ k 10()* 1. k=0 11 3-2i i+1 %3D3 3. >. 5 + V4 12 4. (4)k-1 k%3D1 2. 3.

A: Click to see the answer

*question_answer*

Q: A) For each of these generating functions, find the sequence. 1) त 2) (1-2x)

A: (1) Given generating function is 51+x We have to find the the generating sequence of 51+x We know…

*question_answer*

Q: Find the sequence for the generating functionG (x) = (1-x) 1-x

A: Click to see the answer

*question_answer*

Q: Use the summation formulas to rewrite the expression without the summation notation. n 8i + 5 n2 = 1…

A: The summation is:-

*question_answer*

Q: Match each closed formula, summation notation, and product notation with corresponding sequence,…

A: Click to see the answer

*question_answer*

A: Please refer the attached image for complete solution.

*question_answer*

Q: Express the sum 3 + 5 + 7+ ... + (2k-1) using E-notation.

A: The given sum is 3+5+7+…+2k-1. Express the sum 3+5+7+…+2k-1 using ∑ notation as follows.

*question_answer*

Q: snip

A: ∑i,j=13 ij=∑ i=13∑j=13 ij=∑ i=13i1+i2+i3=11+12+13+21+22+23+31+32+33=1+1+1+2+4+8+3+9+27=56

*question_answer*

Q: Find the partial sum Sn of the sequence an=log(n+5/n+6)

A: Click to see the answer

*question_answer*

Q: in what way is a Riemann sum similar to a Taylor polynomial? (Other than the fact that both can be…

A: We have to write similarities between Riemann sum and Taylor Polynomial.

*question_answer*

Q: 1. By using (For -End) loop find the summation of the next equation for n=2 and 15. 3x4k-1 9* k=1

A: Click to see the answer

*question_answer*

Q: For the sequence defined by: a1 = 2 An+1 = +1 - An Find: %3D %3D a4 = %3D 2]

A: Click to see the answer

*question_answer*

Q: Find the sum of each series. Σ k=1 (k +1)(k +2) (a)

A: (a) The given series is ∑k=1∞2k+1k+2. This implies that, ∑k=1∞2k+1k+2=2∑k=1∞1k+1k+2=2…

*question_answer*

Q: Use iteration to guess an explicit formula for the sequence: ek = 5ek-1 + 2, for all integers k ≥ 2,…

A: Click to see the answer

*question_answer*

Q: 6. Determine the summation notation for the following series: 3+9+27 + 81 +243 b) E=13" c) 25, 3" d)…

A: Click to see the answer

*question_answer*

Q: how to find the reiman sum for f(x)=x^2/10 for the interval [2,6]

A: To determine the Riemann sum (as in integration theory) for the given function over the given…

*question_answer*

Q: Use the recursive formula f(n) = 0.4 ⋅ f(n − 1) + 11 to determine the 2nd term if f(1) = 4.

A: A sequence is a function with the domain being the set of natural numbers and the range being the…

*arrow_forward*

*arrow_forward*

*arrow_forward*